Effect of carp pituitary extract dose and latency period combinations on the stripping response of Clarias batrachus (Linnaeus, 1758) during induced spawning operation - Sahoo, S. K.; Giri, Shiba Shankar; Paramanik, M. (Indian Journal of Fisheries, 2013)
The stripping response of Clarias batrachus was evaluated at five doses of carp pituitary extract (10, 20, 30, 40 and 50 mg kg -1 body weight of female) administration in combination with five latency periods (11, 14, 17, 20 and 23 h). The females did not respond to stripping when injected 10 and 20 mg pituitary dose and stripped respectively at 11-14 and 11 h latency period. A significant (p<0.05) increase in stripping response was observed with increase in hormone doses beyond 30 mg when stripped at 11 h latency. The stripping responses in 30-50 mg pituitary extract at 14-17 h latency were highest and did not vary significantly. Prolonging the latency period beyond 17 h at 30-40 mg pituitary dose also did not affect the stripping response. While stripping the females at 50 mg dose with 20-23 h latency combinations, the stripping response declined. The experiment clearly suggests that stripping response was the best at 14-23 h latency in combination with 30-40 mg pituitary dose.